Narcissistic CEOs and Tools for Mitigating Agency Problems - Bukalska, Elżbieta; Dycha-Wąsik, Gabriela (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: There is little evidence on the choice of tools to mitigate agency problems. Because these tools are chosen by the CEOs (chief executive officers), we believe that their personality matters. We include the narcissism of the CEO to check whether it is an important factor affecting these kinds of decisions. The research aims to determine what tools to mitigate agency problems are chosen by narcissistic CEOs. We consider debt, dividends, and managerial ownership as potential tools for mitigating agency problems. Research Design & Methods: Our sample covers 56 Polish companies over the six years of 2017–2022. We employ linear mixed models analysis. Findings: We find that narcissistic CEOs refrain from ownership in the company they manage. They have no impact on the debt ratio and dividend payouts. Implications / Recommendations: We believe that narcissistic CEOs use managerial ownership tools to diminish their risk (in order not to be associated with it in case something goes wrong). However, this increases the agency problems. Owners should be aware of such behaviour, bearing in mind the negative impact of a narcissistic CEO on the team and work efficiency. Contribution: Our research contributes to the upper-echelon (top management) theory and corporate behavioural finance. The contribution lies in combining corporate finance issues (e.g., agency relation, debt ratio, dividend) and behavioural finance (CEO personal traits).